Bio-orthogonal chemistry-based method for fluorescent labelling of ribosomal RNA in live mammalian cells. Issue 70 (14th August 2019) - Wu, K.; He, M.; Khan, I.; Asare Okai, P. N.; Lin, Q.; Fuchs, G.; Royzen, M.
Abstract : A bio-orthogonal chemistry-based approach for fluorescent labelling of ribosomal RNA is described. Abstract : A bio-orthogonal chemistry-based approach for fluorescent labelling of ribosomal RNA is described. It involves an adenosine analogue modified with trans -cyclooctene and masked 5′-phosphate group using aryl phosphoramidate. The incorporation into rRNA has been confirmed using agarose gel electrophoresis, as well as a highly sensitive UHPLC-MS/MS method. Fluorescent labelling of rRNA has been achieved in live HeLa cells via an inverse electron demand Diels–Alder reaction with a tetrazine conjugated to an Oregon Green fluorophore. This communication describes the stepwise approach that led to the development and characterization of the probe. The results demonstrate a new strategy towards development of future fluorescent probes to investigate the biochemistry of nucleic acids.